2005
DOI: 10.1890/04-0668
|View full text |Cite
|
Sign up to set email alerts
|

Riparian Zones Increase Regional Species Richness by Harboring Different, Not More, Species

Abstract: Abstract. Riparian zones are habitats of critical conservation concern worldwide, as they are known to filter agricultural contaminants, buffer landscapes against erosion, and provide habitat for high numbers of species. Here we test the generality of the notion that riparian habitats harbor more species than adjacent upland habitats. Using previously published data collected from seven continents and including taxa ranging from Antarctic soil invertebrates to tropical rain forest lianas and primates, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
298
0
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(347 citation statements)
references
References 34 publications
20
298
0
11
Order By: Relevance
“…Wet RF buffer zones harbour a special set of species not found in upland forested areas (Sabo et al 2005;Hylander 2006;Sabo and Soykan 2006). In a meta-analysis of 47 studies worldwide (no Nordic studies included) on species richness and composition in both riparian and upland habitats it was found that RF did not host more species than upland habitats.…”
Section: Riparian Forest Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wet RF buffer zones harbour a special set of species not found in upland forested areas (Sabo et al 2005;Hylander 2006;Sabo and Soykan 2006). In a meta-analysis of 47 studies worldwide (no Nordic studies included) on species richness and composition in both riparian and upland habitats it was found that RF did not host more species than upland habitats.…”
Section: Riparian Forest Speciesmentioning
confidence: 99%
“…In fact, the proportional increase in regional species richness due to riparian habitats was on average 38% (Sabo and Soykan 2006). Furthermore, the displacement of species from riparian to upland zones was stronger for plants than animals and stronger in dry than wet climates (Sabo et al 2005). Animals are mobile and can take advantage of seasonally varying microclimates and riparian resources and may therefore utilise both riparian and upland areas.…”
Section: Riparian Forest Speciesmentioning
confidence: 99%
“…In Arizona, USA where wetland environments occupy ∼2% of the land area, ciénegas are critical habitat for at least 19% of the threatened, candidate, or endangered species within the state (Baker et al, 2004). However, beyond species of concern, desert ciénegas and riparian corridors may increase regional biodiversity by up to 50% in some cases (Sabo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Species diversity stems from environmental variation caused by upland influences on the stream, geomorphic channel processes, flood regimes, climate shifts at different altitudes, and the diversity of physical conditions found within the transition zone between terrestrial and aquatic ecosystems [12,13]. For instance, the landscape composition (e.g., presence of forests vs. impervious surfaces) of upland regions can enhance or degrade water quality by influencing the amount of nutrient and sediment runoff [5,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Raedeke [24] reports that nearly 70% of vertebrate species within the surrounding region will use riparian corridors during their lifetime. In addition to microhabitat diversity, riparian habitats increase regional species richness by supporting different species than adjacent upland habitats (i.e., habitats not flanking a riverine, lacustrine, or palustrine system) [13]. For instance, in the Pacific Northwest, piscivorous birds and mammals such as kingfishers (Ceryle alcyon), mergansers (Mergus spp., Lophodytes cucullatus), herons (Ardea spp.…”
Section: Introductionmentioning
confidence: 99%